2001
DOI: 10.1021/jo001685o
|View full text |Cite
|
Sign up to set email alerts
|

N-Functionalized Benzotriazole-1-carboximidoyl Chlorides:  Synthetic Equivalents for Isocyanide Dichlorides

Abstract: Readily prepared N-functionalized benzotriazole-1-carboximidoyl chlorides are proposed as stable and novel isocyanide dichloride synthetic equivalents. Subsequent condensations of these new intermediates afford polysubstituted guanidines, S-aryl isothioureas, and 2-aminoquinazolin-4-thiones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 22 publications
0
17
0
Order By: Relevance
“…Bis(benzotriazolyl) carboximidamide (104) has been developed as a new guanylating agent for the synthesis of tri-and tetrasubstituted guandines 105 [163,164]. Benzotriazolyl carboximidoyl chlorides (106) are stable, colorless, and conveniently handled reagents for the synthesis of unsymmetrical guanidines 107 [165]. Polysubstituted acylguanidines and guanylureas 109 [166] have been prepared from N-acyl-N,Ndisubstituted benzotriazolyl carboximidates 108.…”
Section: Benzotriazole-mediated Imidoylationmentioning
confidence: 99%
“…Bis(benzotriazolyl) carboximidamide (104) has been developed as a new guanylating agent for the synthesis of tri-and tetrasubstituted guandines 105 [163,164]. Benzotriazolyl carboximidoyl chlorides (106) are stable, colorless, and conveniently handled reagents for the synthesis of unsymmetrical guanidines 107 [165]. Polysubstituted acylguanidines and guanylureas 109 [166] have been prepared from N-acyl-N,Ndisubstituted benzotriazolyl carboximidates 108.…”
Section: Benzotriazole-mediated Imidoylationmentioning
confidence: 99%
“…[12,13] The products (guanidines) were obtained in high yields under neutral and mild conditions using an easy purification protocol. [14,15] Benzo-1,2,3-triazol-1-yl-(N-aryl) amidine or monosubstituted (benzotriazole-1-yl) carboximidamide used as a building block for the synthesis of various compounds that have numerous chemical and pharmaceutical applications like mono-and N,N-disubstituted thioureas, N-acyl thioureas [16] besides its use for the preparation of poly substituted acyl guanidines, guanyl ureas, [11] and guanidines. [4,17,18] In addition, (benzotriazole-1-yl) carboximidamides were used to synthesize biologically importance substituted 5-aminotetrazoles [19] and substituted 1,2,4-triazoles.…”
Section: Introductionmentioning
confidence: 99%
“…18 N-Chlorobenzotriazole has been widely used as (i) a mild oxidant 19,20 for the preparation of aldehydes, ketones, 21 azo-compounds, 21 sulphoxides, 20 sulfonimidoyl chlorides, 22 nitrile oxides; 23 (ii) a chlorinating agent 24,25 and (iii) for addition reactions to olefins [26][27][28] and isonitriles. 29 Rees and Storr showed that the reactions of N-chlorobenzotriazole as an oxidant are radical in nature. 26 We now show that N-chlorobenzotriazole (2) conveniently converts aldehydes 1a-g into the corresponding N-acylbenzotriazoles 3a-g (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%